New record of Mock viper – Psammodynastes pulverulentus in Quảng Ngãi region - Thi Thanh, Le (VNU Journal of Science: Natural Sciences and Technology, 2017)
This article summarizes some notes about Mock viper in Quang Ngai region. That have identified species living along streams in natural forests and restoration forest, less distributed in plantations and residential areas. Most snakes live on land and under water; sleep on the tree at night. Mock viper distributed from 55a.s.l to 616a.s.l, average 300 a.s.l. Species often find food on low shrubs and the rock wall along the stream at night, daytime hiding in the hidden niche. Often single species, less active pair species, rare activity of more than 3 individuals. Species found most from February to July. That seen most in Ba Vinh and Ba Dien commune of Ba To district, often met in the evening at 21-30 temperature and 73-84% humidity. The female is higher than males, younger than adults. Habitats of species are strongly affected by overexploitation of forest resources.